2023
DOI: 10.3390/f14102031
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Evaluation of Downy and Silver Birch Wood Quality and Stem Features from a Progeny Trial in Southern Sweden

Grace Jones,
Mateusz Liziniewicz,
Johan Lindeberg
et al.

Abstract: This study investigated whether improved downy birch could perform as well as improved silver birch, and whether there was sufficient genetic variation and control for non-destructive testing (NDT) values to include them as selection traits in breeding programs. NDT tools were applied to a 15-year-old downy birch family trial intermixed with improved silver birch. Average diameters, fissured bark height, and grain angle were higher for silver than downy birch. The genetic analysis for downy birch provided esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…This study showed a negative correlation between MOEdyn calculated by acoustic velocity and wood-density values, with a log of (r = −0.20) and a sample hardness of (r = −0.25). Correlation in both Sweden studies showed a moderate relationship between wood hardness and wood density [10,11]. Similar trends were found in this study of Lithuanian genetic trials.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This study showed a negative correlation between MOEdyn calculated by acoustic velocity and wood-density values, with a log of (r = −0.20) and a sample hardness of (r = −0.25). Correlation in both Sweden studies showed a moderate relationship between wood hardness and wood density [10,11]. Similar trends were found in this study of Lithuanian genetic trials.…”
Section: Discussionsupporting
confidence: 88%
“…These differences may be due to different tree ages and specific growing conditions. Another study in Sweden showed similar mean woodhardness parameters to this study (17.4 mm) for standing trees obtained with a Pilodyn instrument for silver birch [11].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations